JQuery masterclass course : JavaScript and AJAX coding bible - Hussain, Frahaan (Packt Publishing, 2019)
"Learn everything about jQuery Applications and How to Program Them. A step-by-step process is used to show and explain every facet of these topics. This course includes topics such as: What jQuery is? jQuery Certifications; How to program in the jQuery language; Features of the jQuery programming language; Coding Semantics; Website programming; Design practices of applications; Application programming; Network programming. jQuery is one of the most popular programming frameworks in the world that is requested by all companies such as Google, Facebook, and Microsoft. This course will ensure you are not left out as more and more companies request this awesome language. This course will teach you everything about programming jQuery applications and websites."--Resource description page